PENGEMBANGAN KARIR PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN PASAMAN BARAT - Elizar Ramli (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2017)
This research was conducted by the phenomenon at Educational Institution in West Pasaman Regency that indicate a low indicator in the career acceleration. The prupose of this research is getting the information about the career acceleration in Educational Institution in West Pasaman Regency. This study was descriptive research with total of population is 73 employees. The number of sampel is 48 employees. This research used questionnaire with likert scale as data collecting technique. The data was analyzed by determining the mean and the percentage of variable. Based on data analysis, there are several conclusions about the career acceleration in Educational Institution in West Pasaman Regency. They are 1) indicator of training can be categorized as good (81.01%), 2) educational indicator can be categorized as good (82.50%), 3) indicator of rotation can be categorized as good (81.06%), and 4) indicator of promotion can be categorized as enough (80.42%). Overall, the career acceleration in Educational Institution in West Pasaman Regency can be categorized as good (81.25%).Keywords: career acceleration, Educational Institution